Pre-Drinking Behavior of Young Heavy Drinkers - Ogeil, R.; Lloyd, B.; Lam, T.; Lenton, S.; Burns, L.; Aiken, A.; Gilmore, W.; Chikritzhs, Tanya; Mattick, R.; Allsop, S.; Lubman, D. (Informa Healthcare, 2016)
Pre-drinking has been linked to subsequent heavy drinking and the engagement in multiple risky behaviors. Objectives: The present study examined a group of adolescents who recently had a “big night out” to determine whether there were differences in their pre-drinking behavior based on age, gender, geographic location, and social setting. Methods: Participants (n = 351, aged 16–19) representing the heaviest 20–25% of drinkers in their age group were recruited using nonrandom sampling from metropolitan (Melbourne, Sydney, Perth) or regional (Bunbury) locations across Australia and administered a survey by a trained interviewer. Results: Almost half the sample pre-drank (n = 149), most commonly at a friend's house. Those aged 18–19 were more likely to pre-drink, and did so at higher quantities compared to their younger counterparts. Males and females reported similar pre-drinking duration, quantity and amount spent on alcohol. Compared to those in cities, regional participants consumed greater quantities over longer periods of time. Two-thirds of participants consumed alcohol in excess of national guidelines during their pre-drinking session. These participants were more likely to nominate price as a motivation to pre-drink and were less likely to report that someone else provided them alcohol. Conclusions: This study sheds light on the pre-drinking habits of a population of young risky drinkers, and highlights the need for policy makers to address this form of drinking to reduce alcohol-related harm among young people.